As tecnologias de informação e comunicação e o atendimento escolar no ambiente hospitalar: o estudo de uma aluna hospitalizada - Garcia, Simone Hoerbe (2008)
The school assistance in the hospital environment and the information and communication technologies are two themes which are inserted in current discussions on education. The school assistance in the hospital environment is carried out at the hospital class that, according to the National Policy of Especial Education (1994), guarantees the ongoing assessment to children and to youth under risky conditions such as hospital internment and treatment, since hospitalization creates restrictions to close contact relationships and to sociointeractive school opportunities, in other words, it affects the relationship with classmates and the learning relations mediated by the teacher as well as the intellectual exploration of the social life environments. The purpose of this research is to investigate the information and communication technologies as instruments to facilitate learning of hospitalized children. Therefore, a case study with one hospitalized student was carried out. She attended the hospital class from Hospital Universitário de Santa Maria in 2007 and was enrolled in the 4th grade of a school from Maçambará/RS. The instruments of data collection were semi-structured interview with both the hospital class teacher and the student s mother. The analysis of the collected data was based on the theoretical support provided by Vygotsky s socio-historical theory. Based on the analysis, we observed that self-esteem, motivation and socialization of the participant student became evident through the use of information and communication technologies during learning. As a result of that, it was possible to perceive the importance of using the computer as a support tool to the education process since it makes possible to the learner to have access to new knowledge and new ways of thinking and acting by using school materials in a more ludic and interactive way.